Preparation and characterization of poly (methyl methacrylate) / 50% epoxidised natural rubber based solid electrolytes for lithium-ion secondary battery - Abdul Latif, Famiza (2006)
This research focused on the development of new thin film electrolytes based on Poly(methyl methacrylate)(PMMA) / 50% epoxidised natural rubber (ENR 50) blend by solvent casting method. Lithium nitrate (LiNO3), lithium triflate (LiCF3SO3) and lithium imides (LiN(CF3SO2) 2) salts were used as the doping material to provide lithium ion for the ionic conduction. Dimethyl carbonate (DMC), ethylene carbonate (EC) and propylene carbonate (PC) plasticizers were used to improve the physical properties and the morphology of the films. Freestanding films were obtained when PMMA was blended with 10% and 20% of ENR 50. Above these compositions, the films became brittle and bonded strongly to the glass substrate. The blend films were not homogeneous in which the phase separation can be observed in their FESEM micrographs even in the presence of plasticizers. Though the films were not homogeneous, the brittle properties of PMMA film have been improved. The DSC thermograms of these films further confirmed the in-homogeneity of the blends by exhibiting two glass transition temperatures, Tg. The infra red (IR) spectra established the PMMA-ENR 50 interactions and the polymer-salt complexation. Doped PMMA / ENR 50 films with LiNO3 salt were observed to be unstable where by the films obtained became damp and opaque when exposed to the ambient environment. It was observed that the best salt for this PMMA / ENR 50 blend was LiCF3SO3 in which the highest conductivity of 10-5 S/cm at room temperature were obtained. On the other hand, PMMA / ENR 50 / LiN(CF3SO2) 2 electrolyte exhibited the lowest ionic conductivity of 10-7 S/cm at room temperature. The effect of plasticizers differs from one electrolyte system to another. The ionic conduction behaviour in the electrolyte systems depends on the salt and the plasticizers used. The transference number and the modulus formalism showed that the PMMA / ENR 50 blend based electrolytes were ionic conductor. The equivalent circuit for the highest conducting film from each plasticized or non-plasticized electrolyte system was determined using Autolab software. Films with 10-5 S/cm at room temperature were fabricated into LiNiCoO2/ polymer electrolyte / mesocarbon microbeads (MCMB) cell. It was observed that these cells exhibit poor charge-discharge characteristic and can be improved